2010
DOI: 10.1177/0009922810379907
|View full text |Cite
|
Sign up to set email alerts
|

Patient—Provider Communication and Human Papillomavirus Vaccine Acceptance

Abstract: The authors performed telephone interviews of parents of adolescents (n = 430) and their older adolescents (n = 208) in Monroe County, New York to measure parent and adolescent acceptance of human papillomavirus (HPV) vaccine, its association with ratings of provider communication, and vaccine-related topics discussed with the adolescent's provider. More than half of adolescent girls had already received an HPV vaccination, with fewer than one quarter refusing. Parent and teen ratings of provider communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 40 publications
(47 reference statements)
4
45
0
5
Order By: Relevance
“…18,27,71,73,76,80 In addition to age, patients' sex added complexity to communication, with providers offering different prevention messages to boys and girls. 17,22,27,29,35,38,40,76,81 Second, at the interpersonal level, many providers perceived parents as being unsupportive of HPV vaccination, a view which hindered guideline-consistent delivery of recommendations. 12,29,33,35,[37][38][39] Third, studies consistently documented a challenging policy context, including unclear practice guidelines and a lack of school entry requirements for HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…18,27,71,73,76,80 In addition to age, patients' sex added complexity to communication, with providers offering different prevention messages to boys and girls. 17,22,27,29,35,38,40,76,81 Second, at the interpersonal level, many providers perceived parents as being unsupportive of HPV vaccination, a view which hindered guideline-consistent delivery of recommendations. 12,29,33,35,[37][38][39] Third, studies consistently documented a challenging policy context, including unclear practice guidelines and a lack of school entry requirements for HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…80 Studies suggested that parent-adolescent decisions were largely concordant and that most dyads ultimately reached agreement about the vaccination decision, but they sometimes looked to providers for guidance in the case of initial disagreement. 76,81 Interestingly, one qualitative study noted that adolescents' participation in medical dialog was often subtle and included non-verbal forms of communication such as nods, suggesting that adolescents' communication role could be easy to overlook. 76 …”
Section: Communication Rolesmentioning
confidence: 99%
See 3 more Smart Citations